Assessing Myf5 and Lbx1 contribution to carapace development by reproducing their turtle‐specific signatures in mouse embryos. Issue 10 (12th June 2022) - Tekko, Triin; Lozovska, Anastasiia; Nóvoa, Ana; Mallo, Moisés
Abstract: Background: The turtle carapace is an evolutionary novelty resulting from changes in the processes that build ribs and their associated muscles in most tetrapod species. Turtle embryos have several unique features that might play a role in this process, including the carapacial ridge, a Myf5 gene with shorter coding region that generates an alternative splice variant lacking exon 2, and unusual expression patterns of Lbx1 and HGF . Results: We investigated these turtle‐specific expression differences using genetic approaches in mouse embryos. At mid‐gestation, mouse embryos producing Myf5 transcripts lacking exon 2 replicated some early properties of turtle somites, but still developed into viable and fertile mice. Extending Lbx1 expression into the hypaxial dermomyotomal lip of trunk somites to mimic the turtle Lbx1 expression pattern, produced fusions in the distal part of the ribs. Conclusions: Turtle‐like Myf5 activity might generate a plastic state in developing trunk somites under which they can either enter carapace morphogenetic routes, possibly triggered by signals from the carapacial ridge, or still engage in the development of a standard tetrapod ribcage in the absence of those signals. In addition, trunk Lbx1 expression might play a later role in the formation of the lateral border of the carapace. Key Findings: Mouse embryos expressing turtle‐like Myf5 lacking exon2 display alterations in trunk somites resembling features observed in turtle embryos Turtle‐type Myf5 expression is not sufficient to produce mature carapace‐like structures Activation of Lbx1 in trunk somites produce distal rib fusions